Elizabeth Martin Grey’s Delusional Disorder in Helena Fox How It Feels To Float - Cahyaningsih, Wulan; Wahyono, Danu (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2023)
This study is entitled “Elizabeth Martin Grey’s Delusional Disorder in Helena Fox’s How It Feels To Float”. The objective of this research is to examine the mental disorder of Elizabeth or the main character. It uses a qualitative method as the research design and psychological approach as a literary approach. This study aims toexplore and find the causes of delusions and their effects and how Elizabeth overcomes delusions. The results show that Elizabeth’s delusions are caused by the death of her father. She has subjective delusions where she strongly believes that there is no happiness in her life after her father’s death. The effects caused by Elizabeth is experienced disruption on her normal activity, unhappiness in her life, suicidal ideation and self-harm, and also alienation from social life as her delusional disorder’s effects. There are several ways to cope her delusional disorder, namely meditation, counseling, traveling, and seeing a psychiatrist. From the results of this study, the findings indicate that Elizabeth successfully overcomes the delusional disorder that plagued her for the past few years by routinely attending counseling sessions with therapy and meditation, taking medicines and trying to be open to people around her. Keyword: Delusional Disorder, Causes, Effects, Coping.